The Thai Lao – Thailand's largest unrecognized transboundary national ethnicity. Issue 4 (15th April 2019) - Draper, John; Garzoli, John; Kamnuansilpa, Peerasit; Lefferts, Leedom; Mitchell, James; Songkünnatham, Peera
Abstract: In 1900, the Lao ethnonym, and thus the Lao, 'officially' disappeared from Siam. However, Lao culture and identity persisted at local, regional, and national levels. As Keyes (1967) discovered, 'a Northeast Thailand‐based ethno‐regionalism' emerged post‐World War II. This regionalism, which we re‐term 'Thai Lao' and specify to the majority ethnic community, exists in a contested relationship with both 'Thai' and 'Lao' identity. The survival of the Lao ethnic community's cultural identity occurred despite the best efforts of the Royal Thai Government (RTG) to eradicate aspects of Lao culture. These aspects included Lao language, religion, and history, using the school system, the Lao Buddhist Sangha, and the bureaucracy. Beginning in the 1990s, buoyed by a multitude of factors, the Lao ethnic community reappeared as the 'Thai Lao' or 'Lao Isan'. This reappearance was noted in the RTG's Thailand 2011 Country Report (RTG 2011) to the UN Committee responsible for the International Convention on the Elimination of All Forms of Racial Discrimination . For nearly four decades now, 'Laoism' has recurred in Thai academia, the media, the public sphere, popular traditions, and even Lao apocalyptic millenarianism. Following Smith (1986, 1991, 1999), this article utilizes a historical ethno‐symbolist approach to analyse this recurrence.